Factors Affecting Awareness of Oral Cancer: A Cross-Sectional Study from a One-Day Free Consultation Camp in Karachi - Syed Mohsin Abbas Abidi; Syed Imtiaz Ahmed Jafry; Syeda Zeenat Raza Rizvi; Syed Muhammad Zulfiqar Hyder Naqvi (Liaquat National Journal of Primary Care, 2022)
Background: Oral cancer is currently one of the major public health problems globally. Awareness of the risk factors of oral cancers may result in patients seeking medical advice earlier, which in turn can lead to early detection and a better prognosis of such lesions. Literature also reports lack of awareness to be the most common barrier to care-seeking by oral cancer patients. Objective: To determine oral cancer awareness and its associated factors among among dental patients attending free consultation camp in a tertiary care hospital in Karachi. Methods: A cross-sectional study was conducted in a tertiary care dental hospital in district Malir, Karachi, from January 2019 to June 2019. After checking eligibility and taking verbal informed consent, the participants were interviewed using a questionnaire to assess their oral cancer awareness. Data were analyzed on SPSS version 20. Crude and adjusted odds ratio with 95% confidence interval were computed using binary logistic regression to determine the association of demographic characteristics with awareness. Results: The median age of study participants was 37 (IQR=45-29) years whereas 105 (65.2%) of them were female. The mean awareness score of the participants was 8.94±2.71. Moreover, only 34 (21.1%) participants had adequate awareness whereas 127 (78.9%) had inadequate awareness regarding oral cancer. In a multivariable model, education of the patients was found to be associated with adequate awareness regarding oral cancer. Conclusion: It was concluded that certain gaps exist in the awareness of dental patients regarding oral cancer, and apart from the education, none of their demographic characteristics significantly influenced it.